How to manage quarantine—adherence, psychosocial consequences, coping strategies and lifestyle of patients with COVID-19 and their confirmed contacts: study protocol of the CoCo-Fakt surveillance study, Cologne, Germany - Christine Joisten; Annelene Kossow; Julian Book; Lukas Broichhaus; Monika Daum; Nina Eisenburger; Alisa Fabrice; Sven Feddern; Andreas Gehlhar; Anna Carlotta Graf; Barbara Grüne; Markus Lorbacher; et al. (BMJ Open, 2021)
Introduction The current coronavirus (SARS-CoV-2) pandemic has placed unprecedented restrictions on people’s lives and routines. To counteract the exponential spread of this virus, a lockdown was implemented in Germany in March 2020. Infected persons and their contacts were also quarantined. Compliance with quarantine measures is essential for containing the spread of the virus and avoiding incalculable consequences in terms of morbidity and mortality. On the other hand, prolonged homestays, particularly quarantining, may lead to fear, panic, anxiety and depression. Hence, determining the psychological response in people during quarantine and their coping strategies is relevant for the counselling and support of affected persons by healthcare workers.Methods and analysis The CoCo-Fakt-Survey (Cologne-Corona-Beratung und Unterstützung Für Index- und KontAKt-Personen während der Quarantäne-ZeiT; Cologne-Corona counselling and support for index and contacts during the quarantine period—author’s translation) will examine a cohort of persons in Cologne quarantined since the beginning of the SARS-CoV-2 outbreak during March 2020. The questionnaire will include demographic data, transmission route, health status, knowledge of and adherence to quarantine measurements, psychological impact on individuals and their family members including children, mental health status, and lifestyle (physical activity/sedentary behaviour, relaxation techniques, nutrition, smoking). All Cologne residents who needed to be quarantined due to a coronavirus infection and the individuals with whom they had contact will be surveyed.Ethics and dissemination No risks have been identified and no complications are expected. Ethics approval was obtained from the Rheinisch-Westfälische Technische Hochschule (RWTH) Aachen Human Ethics Research Committee (351/20), and the research will be conducted in accordance with the approved protocol. The results will be disseminated through peer-reviewed journals and social medicine conferences.